2013
DOI: 10.1038/ijo.2013.68
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal association of telomere length and obesity indices in an intervention study with a Mediterranean diet: the PREDIMED-NAVARRA trial

Abstract: Background: Telomeres are nucleoprotein structures that protect the ends of eukaryote

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 34 publications
0
75
1
2
Order By: Relevance
“…Por otra parte, muchos de los desequilibrios metabólicos de la obesidad (por ejemplo, glucemia, lipemia, etc.) dan lugar a una disfunción de órganos en una forma que se asemeja al proceso de envejecimiento acelerado (69,74).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Por otra parte, muchos de los desequilibrios metabólicos de la obesidad (por ejemplo, glucemia, lipemia, etc.) dan lugar a una disfunción de órganos en una forma que se asemeja al proceso de envejecimiento acelerado (69,74).…”
Section: Introductionunclassified
“…En un estudio longitudinal con dieta mediterránea (PREDIMED), se mostró por primera vez que una disminución en el riesgo de obesidad está asociado a una longitud telómerica más larga tras una intervención con dieta mediterránea durante cinco años (74). El ritmo de envejecimiento y el equilibrio del peso corporal, por tanto, están interconectados (70).…”
Section: Introductionunclassified
“…Regular physical activity augments the physiological antioxidant response (28,29). Additionally, physical activity promotes energy expenditure and helps maintain energy balance; thus, being physically active may reduce obesity (43) and the associated levels of oxidative stress and inflammation (44). The extent of ROS damage to telomere DNA depends on a balance between factors that promote oxidative stress and those that augment antioxidative defense.…”
Section: Cancer Epidemiol Biomarkers Prev; 25(2) February 2016mentioning
confidence: 99%
“…Leukocyte telomere length, which is a widely used biomarker of aging, has been found to be negatively correlated with body mass index (BMI) (3)(4)(5)(6)(7). Although the observed correlation between BMI and telomere length is relatively weak (r = 0.12) (4), it is remarkable that these studies demonstrated that BMI is associated with an age acceleration effect in blood.…”
mentioning
confidence: 99%